Cutaneous and Ocular Findings in Systemic Pseudohypoaldosteronism I: Early Clinical Pointers - Neha Agarwal; Alpa Gupta; Renu Dhasmana; Ashima Mehta; Nitika Agrawal (JCDR Research and Publications Pvt. Ltd., 2022)
Systemic Pseudohypoaldosteronism type I (PHA I) is an uncommon and an often missed cause of salt wasting crisis in the neonatal period. In addition to dyselectrolytemia, cutaneous findings in the form of miliaria rubra, and ophthalmic findings secondary to abnormal sebum accumulation in the eye may also be present in patients with systemic PHA I. This article is about systemic PHA in a female neonate (birth weight 2.040 Kg, delivered at 34 weeks of gestation), who presented with life-threatening hyperkalemia, along with characteristic cutaneous and ophthalmic manifestations. Normal female genitalia, history of hyperkalemia with similar cutaneous and ophthalmic manifestations leading to death in the previous sibling, provided clue to the diagnosis. All relevant investigations were performed. Blood chemistry in this neonate revealed hyponatremia and hyperkalemia with metabolic acidosis. Plasma renin and serum aldosterone levels were reportedly high. Neonate was followed and electrolytes were monitored twice weekly on outpatient basis. But the life-threatening hyperkalemia led to multiple episodes of vomiting and, refusal to feed for few hours and the baby succumbed to death at age of 2.5 months. Hence, it was concluded that systemic PHA I should be considered in the differential diagnosis of neonates presenting with hyponatremic dehydration, hyperkalemia, and metabolic acidosis. Timely and appropriate electrolyte correction is pivotal for favourable outcome.